DEVELOPING "SEKOLAH PETERNAKAN RAKYAT" PROGRAM USING THE BUSINESS MODEL CANVAS APPROACH (CASE STUDY: BOJONEGORO REGENCY) - Friesgina Wiska; Rizal Syarief; Lukman M. Baga (Indonesian Journal of Business and Entrepreneurship (IJBE), 2016)
SPR Maju Bersama is one of the location where the concept of "Sekolah Peternakan Rakyat (SPR)" is implemented, with the aim to encourage small-scale beef cattle breeder establish a professional collective enterprise under one management. SPR is designed to  change the mindset, knowledge and capability of the beef cattle breeder to become the best and self-reliant  entrepreneurs in the beef cattle business. In the effort to achieve its objective, the organization has not been able to carry out the model business effectively thus new strategies are needed to improve the business model. The objectives of this research are: 1) identify the present business model carried out by SPR Maju Bersama; 2) to carry out SWOT evaluation on each element of the business model; 3) formulate strategic to improve the business model that is formulated in an accurate programs. This research used the combination of business model canvas (BMC) approach and SWOT matrix analysis. The results it is concluded that the SPR Maju Bersama need to improve the business model through alternatives strategies that have been developed include: 1) increase the number of farmer members; 2) apply the concept of "agrosilvopastura" to optimize the management of natural resources; 3) increase the intensity of assistance through e-learning; 4) improve the quality and intensity of the relationship between management and farmers; 5) develop curricula, programs and guide books as well as strengthen the system of membership; 6) expand the partnership by utilizing information technology and existing business partners; 7) establish training centers and services as a resource in the field of SPR and beef cattle; 8) utilizes a strong partnership to change the mindset of farmers; 9) increasing leadership skill and the ability to use communications technology in the management of SPR.Keywords: sekolah peternakan rakyat, Bojonegoro, BMC, matrix SWOT